Impact of Housekeeping Services and Practices on Customer Satisfaction and Repeat Business - Bhatnagar, Ekta; Dheeraj, Nim (Prabandhan: Indian Journal of Management, 2019)
The housekeeping department is the backbone of a hotel. It not only looks after the cleanliness of the whole hotel, but largely contributes towards many other activities in a hotel as well. Keeping an inventory and upkeep of all the accommodation and public areas is a challenge in itself which makes it as one of the crucial departments of a hotel. The guest experience in the hotel is highly modified by the effort being put in by the housekeeping department. The study analyzed the impact of housekeeping services and practices on consumer satisfaction and repeat business. The population chosen for this study was hotels situated in Chandigarh Tri-city which included five, four, and three star hotels of the relevant cities. A total of 150 filled questionnaires from guests in these hotels were collected. The constructs used in the study were: Laundry, Decor, Room Amenities, Cleanliness, Guest Satisfaction, and Repeat Business. All the statements based on the above constructs were measured on a 5-point Likert scale. The results showed a significant amount of internal consistency as well as convergent and discriminant validity. The empirical results supported four hypotheses. Decor and Cleanliness were found to have a significant positive relationship with Guest Satisfaction ; whereas, Laundry services were found to have a positive relationship with Repeat Business. Also, Guest Satisfaction was found to have a positive relationship with Repeat Business.